EXAMINING BING AI AS A SOLUTION TO EFL WRITING FEEDBACK CHALLENGES - Zainurrahman Zainurrahman; Rojab Siti Rodliyah (IKIP Siliwangi, 2024)
This study aims to examine Bing AI (also known as Bing Chat or Copilot) as a feedback agent, focusing on responses to predetermined prompts related to the content score of a research abstract. Two prompts were systematically input, resulting in extended non-corrective feedback from Bing AI which was sensitive to the prompt wording. This study was motivated by challenges in EFL writing feedback provision. Difficulties that teachers face, limitations of peer feedback, and potential drawbacks of Automated Writing Evaluation (AWE) tools were briefly discussed. The results indicate that Bing AI is a promising feedback agent, offering insights into overcoming challenges in feedback provision, specifically in EFL writing instruction. The limitations of the study are also briefly discussed, as well as recommendations for future studies.